Reflections of mental health professionals on working with and in the climate crisis. (4th July 2022) - Samuel, Sophie; Greaves, Natalie; Morgan, Gareth; Li, Ching; Sunglao, Jun Angelo; Belkin, Gary; Henson, Matthew; Salcedo, Sena; Lawrance, Emma L.
Abstract: The aim of this paper is to share our experiences of engaging with the climate crisis as citizens and mental health professionals (MHPs). We hope the outputs will usefully validate the experiences of fellow MHPs and support them to reflect on their role in this crisis. We came together as eight MHPs, participating in group discussions and one-one interviews with the first author to reflect on our experiences. The collaboratively generated themes reflect how engagement with the crisis has: (i) disrupted our personal and professional experiences; (ii) helped us adapt and grow; and (iii) enabled us to live, work and act in more accordance with our values. A key reflection was that these experiences are not linear and we continue to wrestle with our responses to the climate crisis. Discussions also elicited visions of how mental health paradigms could be better adapted to meeting the escalating public health need that this crisis is generating. We conclude by advocating for MHPs to process and respond to the climate crisis and recognize that their skills can make a vital contribution to this global challenge.